Intergenerational educational mobility and cultural practices: a study on cultural stratification using diagonal reference models - Henryk Domański (Ask, 2021)
This study revisits and extends a classic question in sociology and tests three competing hypotheses about the effects of intergenerational educational mobility on cultural tastes. By means of diagonal reference models to data coming from nationally representative survey carried out in 2019, the study shows that mobile individuals come to resemble their nonmobile counterparts in their current educational level which confirms hypothesis of maximization. This is inconsistent with Bourdieu’s view that habitus is largely determined by primary socialization at parental home. The study also demonstrates that upwardly and downwardly mobile individuals switch musical tastes of both parental and current educational level.